2017
DOI: 10.21037/jtd.2017.03.119
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cough syndrome or psychogenic cough—what is the difference?

Abstract: Abstract:The term psychogenic cough has been used to describe cough without obvious medical etiology, which is refractory to medical management and considered to have a psychiatric or psychological basis. This paper outlines the current evidence regarding psychogenic cough, proposes a model for conceptualising psychological issues in chronic cough and discusses strategies for clinical management of psychological issues in patients with chronic cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Psychomorbidity is present in all patients with chronic cough with a variety of aetiologies, and tends to decrease following successful treatment [73]. There are limited criteria for the diagnosis of psychogenic (or somatic) cough and features of psychogenic cough reported in the literature are not unique to psychogenic cough [72].…”
Section: Chronic Cough In Childrenmentioning
confidence: 99%
“…Psychomorbidity is present in all patients with chronic cough with a variety of aetiologies, and tends to decrease following successful treatment [73]. There are limited criteria for the diagnosis of psychogenic (or somatic) cough and features of psychogenic cough reported in the literature are not unique to psychogenic cough [72].…”
Section: Chronic Cough In Childrenmentioning
confidence: 99%
“…5 According to the literature on psychomorbidity among children with chronic cough, anxiety, and depression may be seen either as a result of the chronic cough 13,14 or may exacerbate the symptoms. 4,15 Interestingly, ADHD was the most prevalent disorder in the PFBD group, followed by tic disorders and specific phobias. Therefore, our results showed that there is an increased risk of psychomorbidity in children with PFBD, but the relationship is complex and not pointing to a specific disorder.…”
Section: Discussionmentioning
confidence: 98%
“…According to the literature on psychomorbidity among children with chronic cough, anxiety, and depression may be seen either as a result of the chronic cough or may exacerbate the symptoms . Interestingly, ADHD was the most prevalent disorder in the PFBD group, followed by tic disorders and specific phobias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 The diagnosis of somatic cough syndrome requires the absence of alternative diagnosis after investigation of other diagnoses and the patient meets the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria for a somatic symptom disorder. 74 These DSM-5 criteria include one or more somatic symptoms that are distressing or result in significant disruption to daily life, such as disproportionate and persistent thoughts about the seriousness of the symptoms, high levels of anxiety about symptoms or excessive time and energy devoted to the symptoms. 74 In patients with refractory unexplained chronic cough, American College of Chest Physicians (ACCP) recommendations indicate that the diagnosis of tic cough can be made when the patient presents the core clinical features of tics including suppressibility, distractibility, suggestibility, variability, and the presence of a premonitory sensation whether the cough is single or one of many tics.…”
Section: Other Causes To Considermentioning
confidence: 99%